KEDUDUKAN DAN PERAN TRIUMVIRAT (MENTERI LUAR NEGERI, MENTERI DALAM NEGERI, METERI PERTAHANAN) DALAM PROSES KETATANEGARAAN INDONESIA - , MUHAMMAD ZAKI MUBARRAK ([Yogyakarta] : Universitas Gadjah Mada, 2013)
According to the mandate of Undang-Undang Dasar Negara Republik Indonesia Tahun 1945, Indonesia is the state of law. In the state of law of Indonesia there is a legal gap in the Indonesian Constitution that is interesting to study. That interesting topic is about the position and the function of triumvirate (Foreign Minister, Interior Minister, Defence Minister) with all possibilities of it. This study is aimed at discovering the position of triumvirate in the whole of Indonesian state history according to the Undang-Undang Dasar Negara Republik Indonesia Year 1945, to discover the implementation of triumvirate power when The President and The Vice President are permanently absent, and to discover legal standing in the constitution and the theoretical standing when the âvacuum of powerâ situation is happening in the process of triumvirate succession where the cabinet has been dissolved before. This research used the induction method, with induction logic flow, where the way of thinking would look around the cases which are possible to happen. In this case it started from the position of the triumvirate in the Indonesian state system, moved to the theories, concepts, and the existence of triumvirate in the Indonesian state system which is delivered by the experts of Indonesian state law. The triumvirate concept which became the topic in this research not only belongs to the current regime, but it has existed and been constitutional since the beginning of Indonesian Independence Day, although only in the simple format. In the beginning, the concept of triumvirate was accommodated in Tap. MPR No. VII/MPR/1973 and then it was included in the Undang-Undang Dasar Negara Republik Indonesia Year 1945 in the 4th amendement. Triumvirate exists in the article 8 paragraph (3). In the state practice, triumvirate is constitutionally accepted but there is no case about the triumvirate position as the Presidential executing task. The interesting thing is about the position of the Presidential executing task when the triumvirate has been dissolved. The situation of dissolved triumvirate is only to be resolved by theoretical approach, especially triaspolitica theory or sovereignty theory. It is the only solution because constitutionally there are no rules of it.